DEVELOPMENT OF VIDEO ANIMATION-BASED LEARNING MEDIA TO IMPROVE ELEMENTARY SCHOOL STUDENTS' LISTENING SKILLS - Fitra Itun, Desiana; Widiastuti, Sripit; Fauzi, Adin (Universitas Islam Balitar, 2024)
The objective of this research is to develop animation-based video media suitable for delivering reading materials of three text types (simple procedures, explanations, and objective descriptions) to fifth-grade elementary school students. This research utilizes a Research and Development design, commonly known as developmental research. Due to the ongoing Covid-19 pandemic, readability testing is conducted with 5 fifth- grade students from UPT SD Negeri Talun 05 and 5 elementary school teachers. Data collection techniques include surveys and documentation. Both quantitative and qualitative descriptive analyses are employed for data analysis in this research. The expert assessment of the content yields a 91% rating, categorized as highly feasible. The media expert evaluation results in a 90% rating, indicating the media is highly feasible. The language expert assessment produces an 88% matching category percentage. Students exhibit excellent performance in readability experiments, scoring 90% in the very good category, and they demonstrate a strong preference for animation-based video content. Teachers score remarkably high at 94% in readability testing. Consequently, teachers can consider animation-based media as a reference for Indonesian language learning that covers materials with three text types studied by fifth-grade elementary school classes: simple procedural text, explanation, and objective description.